2015
DOI: 10.1042/bj20150548
|View full text |Cite
|
Sign up to set email alerts
|

Non-β-blocking R-carvedilol enantiomer suppresses Ca2+ waves and stress-induced ventricular tachyarrhythmia without lowering heart rate or blood pressure

Abstract: Carvedilol is the current β-blocker of choice for suppressing ventricular tachyarrhythmia (VT). However, carvedilol’s benefits are dose-limited, attributable to its potent β-blocking activity that can lead to bradycardia and hypotension. The clinically used carvedilol is a racemic mixture of β-blocking S-carvedilol and non-β-blocking R-carvedilol. We recently reported that novel non-β-blocking carvedilol analogues are effective in suppressing arrhythmogenic Ca2+ waves and stress-induced VT without causing brad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 56 publications
4
42
0
1
Order By: Relevance
“…36 Interestingly, both JTV-519 and carvedilol displayed marked SOICR suppression. Other β-blockers (propranolol and labetalol) did not affect SOICR in the CPVT2-hiPSC-CMs, supporting the notion 36,37 that the SR-stabilizing property may be unique to carvedilol. Moreover, flecainide (1 µmol/L) or riluzole, despite possessing important antiarrhythmic actions, failed to significantly suppress SOICR, suggesting that their main antiarrhythmic action may not be related to SR stabilization.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…36 Interestingly, both JTV-519 and carvedilol displayed marked SOICR suppression. Other β-blockers (propranolol and labetalol) did not affect SOICR in the CPVT2-hiPSC-CMs, supporting the notion 36,37 that the SR-stabilizing property may be unique to carvedilol. Moreover, flecainide (1 µmol/L) or riluzole, despite possessing important antiarrhythmic actions, failed to significantly suppress SOICR, suggesting that their main antiarrhythmic action may not be related to SR stabilization.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, carvedilol was suggested to stabilize RyR2 beyond its β-blocking action. 36,37 Similarly, many recent in vivo and clinical studies suggested a potential role for flecainide in CPVT. Two main mechanisms were suggested (1) flecainide may increase triggered-activity threshold by directly blocking Na + channels 39,44,46 or (2) flecainide may stabilize SR thereby decreasing diastolic Ca 2+ leak.…”
Section: Mechanisms Of Antiarrhythmic Drug Activities In the Cpvt2-himentioning
confidence: 99%
“…We have previously shown that carvedilol, a beta-blocker, is able to reduce the duration of openings of single RyR2 channels and suppress RyR2-mediated spontaneous Ca 2ϩ release and stressinduced ventricular tachycardias in a mouse model harboring a CPVT-causing RyR2 mutation (11). We also showed that the non-beta-blocking carvedilol enantiomer, (R)-carvedilol, is also able to suppress spontaneous Ca 2ϩ waves and wave-evoked CPVT without the bradycardia associated with racemic carvedilol (15). Here we demonstrated that racemic carvedilol and the non-beta-blocking (R)-carvedilol enantiomer also suppressed spontaneous Ca 2ϩ oscillations in HEK293 cells expressing the CPVT-and AF-associated RyR2 mutations.…”
Section: Enhanced Ryr2 Ca 2؉ Activation and Cardiac Arrhythmiassupporting
confidence: 48%
“…Mutations Associated with Atrial Fibrillation-We have previously shown that racemic carvedilol, a clinically used betablocker, and the non-beta-blocking (R)-carvedilol enantiomer suppress spontaneous Ca 2ϩ oscillations (SOICR) in HEK293 cells expressing a RyR2 mutation R4496C that is associated with CPVT (11,15). Interestingly, some of the RyR2 mutations located in the central domain, G3946A, M3978I, and Q4159P, have been associated with AF (16,19,23).…”
Section: Racemic Carvedilol and The (R)-carvedilol Enantiomer Suppresmentioning
confidence: 99%
“…Finally, non-β-blocking carvedilol analogues were shown to be effective in suppressing arrhythmogenic Ca 2+ waves and β-adrenergic stress-induced VT in mice with CPVT. [31] Unlike S-carvedilol, which possessing β-blocking activity, the R-carvedilol enantiomer was shown to normalize RyR2 activity without causing bradycardia and hypotension.…”
Section: Discussionmentioning
confidence: 99%